The Study of the Use of the Artistic Resource in Educational Tourism - KOMANDYSHKO, Elena F. (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018DO - 10.14505//jemt.9.4(28).20, 2018)
The author of the article refers to the problem of educational tourism as an artistic resource for modern education. The content of the article is based on the disclosure of different types of cultural and educational tourism and specificity of manifestation of artistic interests and search for the conditions for the realizations cultural and cognitive routes for children and youth. As an example, the technology of “art-pedagogy”, theatrical and game forms of education are presented, and the meaning of the "chronotope" of the path (road) in the context of the artistic resources of educational tourism is considered. The article reveals the essential characteristic of the depictive, plot, socio-historical and meaning-forming meaning of the chronotope. This helps to disclose cultural and historical meanings in terms of space and time. The article shows that the artistic resources of educational tourism are rather versatile and diverse. This contributes to the expansion of needs and development of artistic interest of children and youth.